THE INFLUENCE OF PROBLEM BASED LEARNING ASSISTED BY MIND MAPPING ON STUDENT LEARNING OUTCOMES AND CREATIVE THINKING SKILLS IN CLASS VI SOCIAL STUDIES LESSONS - Siti Nurasiah; Ani Nur Aeni; Nurdinah Hanifah (Universitas Majalengka, 2024)
There are fundamental challenges in learning social studies, one of which is that teachers must use the right strategies, approaches, models and methods to make the learning process more effective. But in reality, teachers still use less varied learning models and methods. Thus resulting in the acquisition of learning outcomes and creative thinking skills of students is low. This study aims to determine the effect of learning outcomes and students' creative thinking skills on social studies lessons in class VI. The method used was quasi-experiment with nonequivalent Control Group Design. The population in this study were all 6th grade students of SDN Sukaraja 01 as many as 60 students. The sample of this study was 2 classes, namely experimental classes and control classes, each class consisting of 30 students. The data collection techniques used were tests and non-tests. Data analysis techniques using Normality Test, homogeneity test, and T test. The results of this study indicate that the problem-based learning model assisted by mind mapping can affect learning outcomes and creative thinking skills of students in social studies lessons. These results are supported by hypothesis testing with the results of the Independent Sample T-Test test showing a significance value (sig.2-tailed) of 0.000 which means <0.05. The results obtained can be concluded that the model and learning methods affect learning outcomes and students' creative thinking skills in social studies lessons in grade VI.